Plate Size and Color Suggestibility: The Delboeuf Illusion’s Bias on Serving and Eating Behavior - Van Ittersum, Koert; Wansink, Brian (Journal of Consumer Research, 2012)
Abstract Despite the challenged contention that consumers serve more onto larger dinnerware, it remains unclear what would cause this and who might be most at risk. The results of five studies suggest that the neglected Delboeuf illusion may explain how the size of dinnerware creates two opposing biases that lead people to overserve on larger plates and bowls and underserve on smaller ones. A countercyclical sinus-shaped relationship is shown to exist between these serving biases and the relative gap between the edge of the food and the edge of the dinnerware. Although these serving biases are difficult to eliminate with attention and education, changing the color of one’s dinnerware or tablecloth may help attenuate them. By showing that the Delboeuf illusion offers a mechanistic explanation for how dinnerware size can bias serving and intake, we open new theoretical opportunities for linking illusions to eating behavior and suggest how simple changes in design can improve consumer welfare.